Study on the luminescence characteristics of Tb3+-doped TeO2-Bi2O3-BaF2 glass for blue-green laser emission. Issue 7 (1st April 2023) - Wu, Tong; Hu, Jiajia; Han, Kexuan; Zhang, Chi; Li, Menglin; Pang, Ruizhen; Hu, Yu; Zhou, Dechun
Abstract: In this study, we prepared Tb 3+ -doped bismuth tellurite glasses by a high-temperature melting method. The matrix glass was characterized by higher thermal stability (ΔT = 102 °C) and lower maximum phonon energy (614 cm −1 ). Based on absorption spectra, Judd-Ofelt analysis revealed the spontaneous radiation transition probability (269.34 s −1 ) and fluorescence branching ratio (41.55%) of 5 D4 → 7 F5 transition. The luminescence peaks of the samples were located at 486 nm and 545 nm blue-green bands. Meanwhile, the luminescence intensity increased with the increase of Tb 3+ concentration and reached the maximum at 4mol% Tb4 O7 . In addition, emission cross-section and gain coefficients were calculated in blue wavelength range, the maximum values were 2.01 × 10 −22  cm −1 and 2.92 cm −1, respectively. Combining all the above results, Tb 3+ doped bismuth tellurite glass had potential application value in the field of blue-green communication.